Beginning Spatial with SQL Server 2008 - Aitchison, Alastair (Apress, 2012)
The use ofspatial data in information systems is hardly a new technology. Dedicated geographic information systems (GISs), such as ARC/INFO from ESRI, have been commercially available since the early 1980s. While the technological capabilities of these systems have evolved significantly over the past 25 years, their adoption has remained relatively confined within a small, specialized group of developers. One reason for this is that, because of the complex nature of spatial data, GIS systems themselves are typically complex, and require dedicated, specially trained operators. Furthermore, these systems are frequently stand-alone systems and do not integrate spatial data with central co rporate data systems. More recently, database management system providers, including Oracle, IBM (DB2), MySQL, and the PostgreSQL Global Development Group, have all released spatially enabled relational database management systems (RDBMSs).Although this has widened the adoption of spatial techniques, the spatial functionality is typically provided using an optional add-in component that requires specific product knowledge that general developers typically do not have yet. Knowledge of spatial data has therefore still largely remained limited to specialist technical fields.